Plato. - Taylor, A. E. (Routledge library editions. Plato., 2012)
Plato's Timaeus was his only cosmological dialogue and for almost thirteen hundred years it provided the basis in the West for educated people's general view of the natural world. The author provides a translation of this important work, together with the Critias - the source of the legendary tale of Atlantis. He has taken particular care to provide an accurate rendering of Plato's words and to avoid putting his own or any other interpretation on the works.